If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + -8 = -2 Reorder the terms: -8 + w = -2 Solving -8 + w = -2 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + w = -2 + 8 Combine like terms: -8 + 8 = 0 0 + w = -2 + 8 w = -2 + 8 Combine like terms: -2 + 8 = 6 w = 6 Simplifying w = 6
| Y=x^2+4x+8 | | 3x*(2x+5)-(x+3)*(3x-1)=1 | | 11z^2+54=36 | | 10x+80=100 | | (3*4)n-9n=39 | | 5.23-(-9.1)= | | X^2=8x-20 | | r^2+4r+6r+24= | | -9.82+(-15.7)= | | m-3=40 | | 12+5=6+23 | | 2x+x+3+x=180 | | X*(x-7)=8 | | 5(b-6)= | | 74+114= | | 2*37= | | 3y-11=3(2y-1)-2y | | -2b+5b-7b= | | 63*63= | | (n-2)*4=24 | | -3b+6b= | | 2b-5b+6b= | | 4x=102 | | 6x+49=8x-5 | | -6r-6r= | | -10=1-3p-5 | | -2j+7j= | | -10x+x^2=-25 | | 3(3x+1)=7(x+1) | | 16=-2x-2x | | 3(3x+1)=7(x+3) | | 2x+x+(x+5)=85 |